Roles of Argonautes and Dicers on Sclerotinia sclerotiorum Antiviral RNA Silencing - Neupane, Achal; Feng, Chenchen; Mochama, Pauline K.; Saleem, Huma; Lee Marzano, Shin-Yi (Frontiers in Plant Science, 2019)
RNA silencing or RNA interference (RNAi) is an essential mechanism in animals, fungi, and plants that functions in gene regulation and defense against foreign nucleic acids. In fungi, RNA silencing has been shown to function primarily in defense against invasive nucleic acids. We previously determined that mycoviruses are triggers and targets of RNA silencing in Sclerotinia sclerotiorum. However, recent progresses in RNAi or dsRNA-based pest control requires more detailed characterization of the RNA silencing pathways in S. sclerotiorum to investigate the utility of dsRNA-based strategy for white mold control. This study elucidates the roles of argonaute enzymes, agl-2 and agl-4, in small RNA metabolism in S. sclerotiorum. Gene disruption mutants of agl-2 and agl-4 were compared for changes in phenotype, virulence, viral susceptibility, and small RNA profiles. The Δagl-2 mutant but not the Δagl-4 mutant had significantly slower growth and virulence prior to virus infection. Similarly, the Δagl-2 mutant but not the Δagl-4 mutant, showed greater debilitation under virus infection compared to uninfected strains. The responses were confirmed in complementation studies and revealed the antiviral role of agl-2. Gene disruption mutants of agl-2, agl-4, Dicer-like (dcl)-1, and dcl-2 did not change the stability of the most abundant endogenous small RNAs, which suggests the existence of alternative enzymes/pathways for small RNA biogenesis in S. sclerotiorum. Furthermore, in vitro synthesized dsRNA targeting agl-2 showed a significantly reduced average lesion diameter (P < 0.05) on canola leaves with agl-2 down-regulated compared to controls. This is the first report describing the effectiveness of RNA pesticides targeting S. sclerotiorum RNA silencing pathway for the control of the economically important pathogen.